Go beyond ‘nudges’ in tackling discrimination - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2013)
In this commentary, SMU Associate Professor of Law and NMP Eugene Tan shared his thoughts on the Fair Consideration Framework (FCF), which was describe by Acting Manpower Minister Tan Chuan-Jin as a “nudge” to employers to give Singaporean professionals, managers and executives (PMEs) – who constitute about a third of the workforce – a “fair chance” at job and development opportunities.